Analisis Risiko Kesehatan Dan Keselamatan Kerja Di Pabrik Tempe Bapak Carmin Dengan Menggunakan Metode Hazard And Operability Study (HAZOP) - Santika Sari Sari; Afifah Wahyu Ramadanti; Mariana Audini (JIE Scientific Journal on Research and Application of Industrial System, 2022)
Hazard and Operability (HAZOP) approach is one of a qualitative methodology risk analysis that is often used for identified the potential danger in the workplace. This research was conducted directly at Carmin’s Tempe Factory by interviewing the workers. Steps in this research are sorting the production process, identified the potential of danger by worksheet hazop, analyzing risk control, monitoring and evaluation, designing improvements, and drawing conclusions. The results showed that there were 18 potential hazards in 8 stages of the tempe-making process at Carmin's factory. Some improvements are needed,  such as equalization of operators for each work station, improvement of workspaces, and the addition of ergonomic tools so that the potential for accidents can be controlled